Provider cost estimation of leptospirosis at district general hospital Monaragala, Sri Lanka - A. M. U. P. Kumari; J. Vidanapathirana; J. Amarasekara; L. Karunanayake (BMC Infectious Diseases)
Abstract Introduction The rising number of leptospirosis patients and escalating healthcare costs strain the sustainability of free healthcare systems in developing countries like Sri Lanka, posing significant challenges to resource allocation and financial stability in these regions. The objective of this study is to assess the healthcare provider’s cost of managing leptospirosis at the District General Hospital, Monaragala, Sri Lanka. Methods A hospital-based cost estimation study was conducted in DGH Monaragala using the scenario building technique, to assess the provider cost of laboratory confirmed leptospirosis patients using three standard management profiles as uncomplicated ward treated, complicated ward treated and ICU treated. Results The provider cost per uncomplicated leptospirosis patient treated in the ward was Rs. 5,449.39 per day (Rs. 5,993 with 10% inflation), totaling Rs. 21,797.54 for an average 4-day stay (Rs. 23,976 with inflation). For complicated cases, the cost per day was Rs. 5,695.35 (Rs. 6,264 with 10% inflation), with a total of Rs. 39,867.43 for an average 7-day stay (Rs. 43,853 with inflation). ICU costs varied by complication: renal (Rs. 26,538.79/day), cardiac (Rs. 28,212.39/day), pulmonary (Rs. 29,657.10/day), neurological (Rs. 26,444.85/day), and multi-organ failure (Rs. 28,363.17/day). The total provider cost for laboratory-confirmed leptospirosis cases at DGH Monaragala was Rs. 7,916,564.52, with 34.7% allocated to managing 11 complicated ICU cases. Conclusions and recommendations The provider cost of leptospirosis in DGH Monaragala was high. Given the inherent challenges in limiting exposure, it is imperative that control efforts prioritize early detection and treatment.